Methylglyoxal impairs human dermal fibroblast survival and migration by altering RAGE-hTERT mRNA expression in vitro - Nurul Muhammad Prakoso; Ayu Mulia Sundari; Fadhilah; Abinawanto; Anantya Pustimbara; Astari Dwiranti; Anom Bowolaksono (Toxicology Reports)
Fibroblasts are native residents in dermal layer of human skin which are important for dermal regeneration and essential during cutaneous wound healing by releasing inflammatory markers and actively migrate to close an open wound. Premature skin ageing due to methylglyoxal (MGO) has recently caught the attention considering its potential to accelerate the emergence of skin ageing signs, however previous studies were only focused in primary neonatal dermal fibroblast and NIH3t3 fibroblast cell line. Therefore, thorough investigation is required to study the impact of MGO on primary human dermal fibroblast isolated from adult subject (HDFa). In our experiments, short exposure of MGO was observed to induced significant reductions in cell viability at concentrations of 7.5, 10, 12.5, 15, and 17.5 mM (p < 0.005) after 3 hours of treatment. The cellular death of HDFa at 10, 12.5 and 15 mM of MGO were also marked by increased in intracellular ROS level, indicating the involvement of oxidative stress-induced death in these cells. We also observed enlarge scratch areas of cells exposed with 7.5 and 10 mM MGO compared to control after 26 hours, thereby suggesting a decline in cell migration and viability in this group. We propose the increased ROS as the consequence of AGE-RAGE activation which was marked by significant elevation of RAGE mRNA on cells exposed to 10 mM MGO. Our data also suggest the occurrence of DNA damage events via ROS-induced oxidation or mediated by decline in hTERT mRNA expression.